Missionaries in a globalized world: catholic communities in Argentina and the making of new catholic citizenships - Gimenez Beliveau, Veronica (2009)
This article examines contemporary orthodox or traditionalist communities that have emerged within the heart of Argentinean Catholicism. The discussion aims to contribute to current debates concerning global religious citizenships in relation to orthodox or traditionalist Catholic communities. Vigorously promoted by Pope John Paul II and now Benedict XVI, such conservative communities have exceeded the nation-state boundaries in which they have arisen and, using global resources from diverse international networks within the Roman Catholic church, they work hard to expand still further throughout the globe. Conservative Catholic communities, which ground their activities in the Second Vatican Council (1962–1965), have found in Argentina conditions particularly favorable for growth. While Argentinean Catholics who participate in such groups are still a clear minority, they currently enjoy a visibility in the public sphere and recognized space within the Catholic church. As they justify their expansion, the communities redefine both the goal and the appropriate territories for missionization. The construction of Catholic community draws on perceptions of a memory of Christianity that go beyond national loyalties, generating for participants new worldviews and forms of sociability within the frame of a “renewed” Catholicism.